2019
DOI: 10.28945/4441
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Subjective Learning Effectiveness of Serious Games

Abstract: Aim/Purpose: This work examines which factors influence user views on the learning effectiveness of serious games. For that matter, a model was developed and tested. Background: Although the impact of serious games on learning is their most widely ex-amined aspect, research is spread thin across a large number of studies having little in common in terms of their settings, samples, and learning sub-jects. Also, there is a lack of consensus regarding which factors have an im-pact on their effectiveness. The mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 90 publications
1
35
0
3
Order By: Relevance
“…Besides demographic information (such as age, gender, scientific background, ICT and game-playing competence), respondents were asked to indicate their agreement to fifty-four statements in a five-point Likert-type scale (worded strongly agree to strongly disagree). Its reliability and factorial structure were tested and confirmed in previous studies (Fokides, Kaimara, Deliyannis, & Atsikpasi, 2019;Fokides, Atsikpasi, Kaimara, & Deliyannis, 2019a, 2019bKaimara, Fokides, Plerou, Atsikpasi, & Deliyannis, 2020). The questionnaire's items of the "Scale for Measuring the Learning Experience in Serious Games" are presented in the Appendix.…”
Section: Instrumentmentioning
confidence: 65%
See 2 more Smart Citations
“…Besides demographic information (such as age, gender, scientific background, ICT and game-playing competence), respondents were asked to indicate their agreement to fifty-four statements in a five-point Likert-type scale (worded strongly agree to strongly disagree). Its reliability and factorial structure were tested and confirmed in previous studies (Fokides, Kaimara, Deliyannis, & Atsikpasi, 2019;Fokides, Atsikpasi, Kaimara, & Deliyannis, 2019a, 2019bKaimara, Fokides, Plerou, Atsikpasi, & Deliyannis, 2020). The questionnaire's items of the "Scale for Measuring the Learning Experience in Serious Games" are presented in the Appendix.…”
Section: Instrumentmentioning
confidence: 65%
“…In order to evaluate UX, to examine the possible statistically significant differences among users and to record if users pay attention to different aspects of games according to their particular characteristics, the SGs' type (2D or 3D) and the quality of human-game interaction were taken into account. In our previous researches (Fokides, Kaimara, Deliyannis, & Atsikpasi, 2019;Fokides, Atsikpasi, Kaimara & Deliyannis, 2019a, 2019bKaimara, Fokides, Plerou, Atsikpasi, & Deliyannis, 2020), we concluded that twelve factors can be used for assessing SGs: immersion, enjoyment, perceived usefulness-knowledge improvement, perceived narratives' adequacy, perceived realism, perceived feedback's adequacy, perceived audiovisual adequacy, perceived relevance to personal interests, perceived goal's clarity, perceived ease of use, adequacy of the learning material and motivation. In the present study, learners' experience was evaluated via a questionnaire which examined the above factors (see Appendix).…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Undisputable fundamental factors in the educational process, i.e., teaching–learning, are teachers and learners. Authors’ previous studies examined learners’ views regarding digital educational games (Fokides et al, 2018 , 2019a , b ; Kaimara et al, 2019a , 2020a , b ). Regarding the role of teachers, it is concluded that there have been several studies on teachers' (pre-service and in-service) attitudes towards ICT integration in schools, and their willingness to use innovative technology but not a sufficient number of studies on their intention to integrate gaming literacy within educational goals in Greece (Megagianni & Kakana, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Παράρτημα). Η κλίμακα αξιολόγησης SGES, η οποία αξιολογεί ταυτόχρονα πολλά δομικά στοιχεία των παιχνιδιών που διαμορφώνουν τις απόψεις των χρηστών όταν παίζουν παιχνίδια, ελέγχθηκε για την εγκυρότητα και την αξιοπιστία της μέσω πολλαπλών στατιστικών αναλύσεων (Fokides et al, 2019a, 2019b.…”
Section: διαμορφωτική αξιολόγησηunclassified